A high‐resolution atmospheric dust record for 1810–2004 A.D. derived from an ice core in eastern Tien Shan, central Asia. Issue 14 (24th July 2017) - Zhang, Wangbin; Hou, Shugui; Liu, Yaping; Wu, Shuangye; An, Wenling; Pang, Hongxi; Wang, Chaomin
Abstract: Centennial‐scale, high‐resolution records of atmospheric dust conditions are rare in the arid and semiarid regions of central Asia, limiting our understanding of the regional climate and environmental changes and their potential driving forces. In this paper, we present an annually resolved atmospheric dust record covering the period of 1810–2004 A.D., reconstructed from an ice core retrieved at 4512 m above sea level from the Miaoergou Glacier in the eastern Tien Shan. The time series of dust flux for the past 195 years shows three periods of relatively low values (i.e., 1810–1829 A.D., 1863–1940 A.D., and 1979–2004 A.D.) and two periods of relatively high values (i.e., 1830–1862 A.D. and 1941–1978 A.D.). Spatial correlation analysis suggests possible regional factors controlling the dust flux, including antecedent summer precipitation, spring soil moisture, and near‐surface wind speed. In addition, the Miaoergou dust flux is closely associated with the winter index of the North Atlantic Oscillation (NAO) over the past two centuries, with high (low) dust periods coinciding with the negative (positive) phases of the NAO. The persistent relationship suggests that the NAO may have been a key driver on dust flux change over the arid regions between the Tien Shan and Kunlun Mountains. Key Points: First high‐resolution centennial‐scale (1810–2004 A.D.) dust record from Miaoergou Glacier, eastern Tien Shan Regional factors affecting dust flux include precipitation, spring soil moisture, and spring surface wind speed The NAO is a potential key driver of dust emissions over the arid regions in the northwestern China